THE IMPLEMENTATION OF REGULATION OF THE MINISTER OF RELIGIOUS AFFAIRS OF THE REPUBLIC OF INDONESIA NUMBER 12 YEAR 2016 REGARDING THE MANAGEMENT OF NON-TAX STATE REVENUES ON MARRIAGE FEE OR RECONCILIATION OUTSIDE THE DISTRICT OFFICE OF RELIGIOUS AFFAIRS AT THE DISTRICT OFFICES OF RELIGIOUS AFFAIRS IN BENGKULU CITY - Budi Hartono; Sirman Dahwal; M. Darudin (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
One of the sources of non-tax state revenues from the District Office of Religious Affairs comes from the marriage fees that are carried out outside the District Office of Religious Affairs, as stipulated in the Regulation of the Minister of Religious Affairs of the Republic of Indonesia Number 12 Year 2016. This Regulation of the Minister of Religious Affairs is applied in all District Offices of Religious Affairs in every City or Regency in Indonesia. The formulations of the problem investigated in this study were: (1) How was the Implementation of the Regulation of the Minister of Religious Affairs of the Republic of Indonesia Number 12 of 2016 concerning the Management of Non-Tax State Revenues on Marriage Fees or Reconciliation Outside the District Office of Religious Affairs in the District Offices of Religious Affairs in Bengkulu City?; (2) Was the marriage cost outside the District Office of Religious Affairs paid by the bride and groom outside the provisions of the Regulation of the Minister of Religious Affairs of the Republic of Indonesia Number 12 year 2016 concerning the Management of Non-Tax State Revenues on Marriage Fees or Reconciliation Outside the District Office of Religious Affairs can be classified as gratification acts y as regulated in Law of the Republic of Indonesia Number 20 year 2001 concerning Corruption Crimes?. The research method used to address these problems was the empirical juridical research method. The results of this study indicated that: (1) The regulation of the Minister of Religious Affairs Number 12 year 2016 concerning the Management of Non-Tax State Revenues on Marriage Fee and/or Reconciliation Outside the District Office of Religious Affairs, has been implemented at the District Offices of Religious Affairs of Bengkulu City, namely, in terms of the provisions for marriage fees, deposits and receipts, disbursements, uses and reporting. (2) Marriage Fees or Reconciliation Outside the District Office of Religious Affairs, especially in the case of the Headman, or the Head of the District Office  of Religious Affairs, or Officers who received money when carrying out services for the implementation of marriage contract counseling outside the District Office of Religious Affairs, cannot be classified as gratification acts as regulated in the Law of the Republic of Indonesia Number 20 Year 2001 regarding Corruption Crime.